Análisis no lineal de la respuesta sísmica de taludes sumergidos - Cardona Giraldo, Luz Catalina (My University, 2008)
Análisis no lineal de la respuesta sísmica de taludes sumergidos
Keywords: Análisis no lineal de la respuesta sísmica de taludes sumergidos